The Effectiveness of Picture-Based Instruction in Enhancing EFL Vocabulary Mastery: A Qualitative Study at Islamic Junior High School in Indonesia - Rahmadani, Amalia; Suhendi, Andang; Lestari, Triana; Umami, Risa (JOURNAL OF LANGUAGE, 2026)
This study investigates the use of pictures as instructional media for teaching English vocabulary to second-year students at MTs Ta’dib Al-Mu’allimin Al-Islamy. Vocabulary mastery is a fundamental component of language learning; however, many students face difficulties in understanding and retaining new words. Therefore, the use of visual media, particularly pictures, is considered an effective strategy to facilitate vocabulary acquisition. This research adopts a qualitative study design, aiming to provide an in-depth understanding of how picture-based instruction is implemented and how it influences students’ vocabulary learning. Data were collected through classroom observations, documentation, questionnaires, and vocabulary tests to obtain both descriptive and supportive quantitative evidence. The combination of these instruments allows for data triangulation to enhance the validity of the findings. The results indicate that the use of pictures significantly improves students’ vocabulary mastery and increases their engagement in the learning process. Visual media help students comprehend meanings more easily, retain vocabulary more effectively, and participate more actively in classroom activities. Furthermore, the results of the vocabulary tests show a noticeable improvement in students’ scores after the implementation of picture-based instruction, with the majority of students achieving scores above the minimum mastery criterion (KKM). Therefore, the use of pictures is an effective and engaging instructional medium for teaching vocabulary. It not only enhances students’ understanding and retention but also fosters active participation in the classroom. Therefore, teachers are strongly encouraged to integrate visual media into their teaching strategies to support students’ vocabulary development.